Marfan syndrome with ascending aortic aneurysm: Value of cardiac computed tomography - Pedro Jerónimo Sousa; Pedro Araújo Gonçalves; Sérgio Boshoff; Hugo Marques; Salomé Carvalho; João Moradas Ferreira; Miguel Mota Carmo; Ana Aleixo; José Pedro Neves; Miguel Mendes (Revista Portuguesa de Cardiologia, 2013)
We report the case of a 40-year-old man with known Marfan syndrome who presented with severe aortic valve regurgitation secondary to significant aortic root dilatation. To rule out coronary artery disease and to evaluate the rest of the thoracic aorta before surgery, cardiac computed tomography (CT) was performed. A brief review of the literature shows how cardiac CT can, in selected cases, rule out coronary artery disease before non-coronary cardiothoracic surgery. Resumo: Descrevemos o caso de um doente de 40 anos de idade com Síndrome de Marfan, que apresenta regurgitação valvular aórtica grave, secundária a dilatação severa da raiz aórtica. Para excluir a presença de doença coronária e estudar os restantes segmentos aórticos antes da cirurgia, foi realizada uma angioTC cardíaca.Uma breve revisão da literatura demonstra como, em determinados contextos, a angioTC cardíaca pode ter vantagens na exclusão de doença coronária antes de cirurgia cardio-torácica não coronária. Keywords: Cardiac CT, Marfan syndrome, Aortic aneurysm, Palavras-chave: AngioTC cardíaca, Síndrome de Marfan, Aneurisma da aorta